Health Information Systems Is our Focus Correct? - Bréant, C.; Section Editor for the IMIA Yearbook Section on Health Information Systems (Yearbook of Medical Informatics, 2011)
Summarize excellent current research in the field of Health Information Systems.Synopsis of the articles selected for the IMIA Yearbook 2011.Five papers from international peer reviewed journals have been selected for the section on health information systems.The selected articles illustrate that strategic, organizational and human aspects require specific attention in order to increase HIS adoption, and to demonstrate value in supporting the needs of clinicians and their patients.
Keywords: Medical informatics; International Medical Informatics Association; health information systems; hospital information systems